'Conundrum of esoterica': on the long-forgotten genus Eutittha Thorell, 1878, with new taxonomic considerations in Cheiracanthium C. L. Koch, 1839 (Araneae: Cheiracanthiidae). Issue 19 (18th May 2020) - Esyunin, Sergei L.; Zamani, Alireza
ABSTRACT: The status of the poorly known spider genus Eutittha Thorell, 1878 which has been overlooked for more than 60 years is investigated. Examination of the type material of Eutittha insulana Thorell, 1878 (type species of the genus, currently classified in Cheiracanthium, with new designation of lecto- and paralectotype) revealed the misidentification of this species since 2001. As a result, Eutittha stat. resurr . is removed from the synonymy of Cheiracanthium, diagnosed and redescribed, with the inclusion of two species groups and nine species: E. insulana Thorell, 1878 comb. nov . (♀, Indonesia), E. brevicalcarata (L. Koch, 1873) comb. nov . (♂♀, Australia, Indonesia), E. excavata (Rainbow, 1920) comb. nov . (♀, Australia), E. lanceolata (Chrysanthus, 1967) comb. nov . (♀, Indonesia), E. lompobattangi (Merian, 1911) comb. nov . (♂, Indonesia), E. marplesi (Chrysanthus, 1967) comb. nov . (♂♀, Indonesia), E. mordax (L. Koch, 1866) comb. nov . (♂♀, Samoa, Australia; doubtful records from Tonga and French Polynesia), E. stratiotica (L. Koch, 1873) comb. nov . (♂♀, Australia, Tasmania, New Zealand) and E. submordax (Zhang, Zhu & Hu, 1993) comb. nov., stat. resurr . (♂♀, China, Japan, Taiwan) (all ex. Cheiracanthium ). The taxonomic status of the other 12 Cheiracanthium species described by Thorell in Eutittha is discussed. Seven species groups in Cheiracanthium are proposed and diagnosed here, and new taxonomic data are provided for five species: (1) C. iranicum sp. nov . (♂, Iran) is described as a new species, (2) C. adjacensoides Song, Chen & Hou, 1990 stat. resurr . (♂♀, southeast Asia) is removed from the synonymy of E. insulana, and C. payateus Barrion & Litsinger, 1995 syn. nov . is recognized as junior synonym of C. adjacensoides ; C. tingilium Barrion & Litsinger, 1995 syn. nov ., C. bikakapenalcolium Barrion & Litsinger, 1995 syn. nov . and C. hugiscium Barrion & Litsinger, 1995 syn. nov . are now all considered as junior synonyms of C. adjacensoides and thus are removed from the synonymy of E. insulana, (3) Cheiracanthium andamanense (Tikader, 1977) comb. nov., stat. resurr . (♀, India, ex. Clubiona ) is removed from the synonymy of C. turiae Strand, 1917, and (4) C. sadanai Tikader, 1976 stat. resurr . (♂♀, India) is removed from the synonymy of C. melanostomum. http://www.zoobank.org/urn:lsid:zoobank.org:pub:85C6DF25-BB22-42D7-AB72-35BD1AAD1507